Adiponectin Prevents Diabetic Premature Senescence of Endothelial Progenitor Cells and Promotes Endothelial Repair by Suppressing the p38 MAP Kinase/p16(INK4A) Signaling Pathway - Chang, Junlei (American Diabetes Association, 2010)
OBJECTIVE: A reduced number of circulating endothelial progenitor cells (EPCs) are casually associated with the cardiovascular complication of diabetes. Adiponectin exerts multiple protective effects against cardiovascular disease, independent of its insulin-sensitizing activity. The objective of this study was to investigate whether adiponectin plays a role in modulating the bioavailability of circulating EPCs and endothelial repair. RESEARCH DESIGN AND METHODS: Adiponectin knockout mice were crossed with db(+/−) mice to produce db/db diabetic mice without adiponectin. Circulating number of EPCs were analyzed by flow cytometry. Reendothelialization was evaluated by staining with Evans blue after wire-induced carotid injury. RESULTS: In adiponectin knockout mice, the number of circulating EPCs decreased in an age-dependent manner compared with the wild-type controls, and this difference was reversed by the chronic infusion of recombinant adiponectin. In db/db diabetic mice, the lack of adiponectin aggravated the hyperglycemia-induced decrease in circulating EPCs and also diminished the stimulatory effects of the PPARγ agonist rosiglitazone on EPC production and reendothelialization. In EPCs isolated from both human peripheral blood and mouse bone marrow, treatment with adiponectin prevented high glucose–induced premature senescence. At the molecular level, adiponectin decreased high glucose–induced accumulation of intracellular reactive oxygen species and consequently suppressed activation of p38 MAP kinase (MAPK) and expression of the senescence marker p16(INK4A). CONCLUSIONS: Adiponectin prevents EPC senescence by inhibiting the ROS/p38 MAPK/p16(INK4A) signaling cascade. The protective effects of adiponectin against diabetes vascular complications are attributed in part to its ability to counteract hyperglycemia-mediated decrease in the number of circulating EPCs.